Reviewed book: Fenomenología, formación y mundo de la vida. Problemas teóricos y metodológicos de la fenomenología. Author: Germán Vargas Guillén - Aguirre García, Juan Carlos (Estudios de Filosofía, 2012)
The first part is titled: “Phenomenology of phenomenology”, an issue that has been present since the very origins of phenomenology and the constant concern of its founder. In this part, three very diverse studies are addressed, the axis of which is the interest in contributing, without the pretension of systematicity, to a meta phenomenology. In the first study, the author approaches one of the most vital questions of phenomenology, that is, whether or not there is a phenomenological method. After clarifying the historical, epistemological, and methodological difficulties (the latter called by the author “procedural”) to dare to answer this question, Vargas Guillén arrives at the thesis of his study: “Phenomenology, which is essentially a method, has principles , but not procedures” (p. 14). In a clear way, difficult to find in most phenomenological texts, and supported by didactic schemes, the author dedicates himself to explaining each of the “postulates or methodological principles of phenomenology”, closing the study with some controversial suggestions.